KINERJA ORGANISASI UPTD BALAI PERBENIHAN DAN PERSUTERAAN ALAM DINAS KEHUTANAN DAERAH PROVINSI SULAWESI UTARA - PANGKEY, SILFIA ANASTASIA; PRATIKNJO, MARIA HENY; TULUSAN, FEMMY (JURNAL ADMINISTRASI PUBLIK, 2019)
Regional Technical Implementation Unit Center for Natural Seed and Silk North SulawesiProvincial Forestry Service is one of the bureaucratic organizations that has in the Development andDevelopment of Natural silk in order to improve people's welfare. The technical bureaucraticorganization have not achieved optimal performance in carrying out tasks in the absence of silk threadproduced in accordance with planning. This study aims to analyze why the organization RegionalTechnical Implementation Unit Center for Natural Seed and Silk North Sulawesi Provincial ForestryService in carrying out the tasks of the development and development of natural silk in the context ofimproving the welfare of the community, no results have been obtained in accordance with the plan.This study uses qualitative methods with descriptive analysis Descriptive done in Regional TechnicalImplementation Unit Center for Natural Seed and Silk North Sulawesi Provincial Forestry Service Thedata used in this study are primary and secondary data. Data collection in this study was carried out withthree main activities, namely interviews, observation and documentation.The results of this study indicate that the productivity indicators, the performance of RegionalTechnical Implementation Unit Center for Natural Seed and Silk North Sulawesi Provincial ForestryService has been implemented efficiently but has not been fully effective, because there are resultsobtained but not in accordance with the expected planning that is producing high-quality and high-sellingsilk thread. This happens because it has not been supported with adequate human resources, budget andinfrastructure in the process of carrying out the silkworm cultivation.Keywords: Organizational Performance, Natural silk